An aeroacoustic study of the flow surrounding the front of a simplified ICE3 high-speed train model. (March 2020) - Minelli, G.; Yao, H.-D.; Andersson, N.; Höstmad, P.; Forssén, J.; Krajnović, S.
Abstract: A numerical study using IDDES is carried out to investigate the aerodynamic and the aeroacoustic response of a simplified ICE3 high-speed train model. The work focuses on the front part of the train and, in particular, on the first bogie cavity. The choice is justified by a literature survey which shows that this part of the train is the principal contributor of critical noise pollution created at pass-by in populated areas. Detailed CFD can provide useful insight and be of great importance in the identification of noise generation mechanisms and their relation with the flow structures. Results show the formation of two main aerodynamic structures with a clear relation to the aeroacoustic response calculated on the train and ground surfaces. Simulations were made at Re = 1 . 8 × 10 5 and M = 0.058 to match the experimental observations found in literature and generate a set of benchmark data for future investigations.